Early learning to concentrate intake in Huacaya alpacas - Castro Bedriñana, Jorge Isaac (2017)
The study aimed to determine the age of Huacaya alpacas in early learning to concentrate intake under maternal influence, based on the susceptibility of young alpacas of not eating concentrates due to neophobia. The study was conducted in the central highlands of Peru, with 30 baby alpaca (and their mothers), divided into three groups of 10 animals of 2, 3 and 4 months of age per group. The baby alpacas were offered a concentrate for 15 days based on wheat byproduct, ground barley, cotton pulp, molasses and minerals and the daily acceptance was assessed. Eighty per cent of 4-month animals accepted the concentrate at 8.8 ± 0.5 days (p <0.05). At day 11, only 4 of the 2-month animals accepted the concentrate, but all accepted it at day 13, while all 3-month old animals accepted concentrate at day 11. Concentrate intake was standardized at an earlier stage (10.0 ± 1.0 days) in 4-month old while for the 2 and 3-month old animals were at 12.6 ± 0.9 and 12.0 ± 1.0 days respectively (p<0.05). Voluntary intake was higher in 3-month old animals (56.7 ± 18.5 g; p <0.05), showing that the best age for early learning concentrate consumption was three months.